The water absorption, mechanical and thermal properties of chemically treated woven fan palm reinforced polyester composites - Kusmono; H. Hestiawan; Jamasri (Journal of Materials Research and Technology, 2020)
This study aims to investigate the effect of silane, alkali, and a combination of alkali–silane treatments on the water absorption behavior, mechanical and thermal properties of woven fan palm fibers (WFP)-reinforced unsaturated polyester composites. Maximum moisture content (Mm) and diffusivity (D) values of treated WFP composites immersed in 3.5% NaCl solution both at room temperature and 60 °C were found to be lower than those of untreated WFP composite. The water absorption patterns of the composites immersed at room temperature were found to follow Fickian behavior, contrary to those immersed at 60 °C. The chemical treatments enhanced significantly the tensile and flexural strength of WFP composites. The water absorption reduced drastically the tensile, flexural, and impact strength of WFP composites. The tensile, flexural and impact strength of the treated composites immersed at 60 °C was lower than at room temperature. The thermal stability of alkali-treated WFP composite was slight higher than that for the untreated and silane-treated WFP composites.